Structure-aided optimization of 3-O-β-chacotriosyl epiursolic acid derivatives as novel H5N1 virus entry inhibitors. Issue 22 (15th November 2020) - Li, Sumei; Jia, Xiuhua; Li, Hui; Ye, Yilu; Zhang, Xuesha; Gao, Yongfeng; Guo, Guoqing; Liu, Shuwen; Song, Gaopeng
Graphical abstract: Highlights: A series of 3-O-β-chacotriosyl epiursolic acid derivatives were synthesized. These saponins showed strong anti-H5N1 activity in vitro . Intensive SARs studies were conducted. These saponins could block the invasion of H5N1 viruses into host cells. Abstract: It is urgent to develop new antiviral agents due to the continuous emergence of drug-resistant strains of influenza virus. Our earlier studies have identified that certain pentacyclic triterpene saponins with 3-O-β-chacotriosyl residue are novel H5N1 virus entry inhibitors. In the present study, a series of C-28 modified 3- O -β-chacotriosyl epiursolic acid derivatives via conjugation with different kinds of sides were synthesized, of which anti-H5N1 activities in A549 cells were evaluated in vitro . Among them, 10 exhibited strongest anti-H5N1 potency at the low-micromole level without cytotoxicity, surpassing the potency of ribavirin. Further mechanism studies of the lead compound 10 based on HI, SPR and molecular modeling revealed that these new 3-epiursolic acid saponins could bind tightly to the viral envelope HA protein, thus blocking the invasion of H5N1 viruses into host cells.